Role of general practice in the diagnosis of oral cancer. Issue 2 (February 2016) - Crossman, Timothy; Warburton, Fiona; Richards, Michael A.; Smith, Helen; Ramirez, Amanda; Forbes, Lindsay J.L.
Abstract: The incidence of oral cancer is increasing in the United Kingdom. There is evidence that early diagnosis and effective treatment improve survival, but the poor 5-year survival rate (50%), which has not improved for several decades, has been attributed to advanced stage at presentation. To investigate the symptoms associated with cancer of the oral cavity and to explore the role of general practitioners (GP) in the identification and referral of patients, we sent 200 patients questionnaires on the route to diagnosis, symptoms, delay in presentation, and outcomes of consultations with their GP. Of 161 respondents, over half (56%) had been referred to secondary care by their GP and a third (32%) by their dentist. The most commonly reported symptoms were a mouth ulcer (32%), a lump in the face or neck (28%), and pain or soreness in the mouth or throat (27%). Fifteen per cent delayed presentation for more than 3 months. After consultation with a GP (n=109), 53% were referred to a specialist, 22% were referred for tests, 12% were told that their symptom was not serious, and 12% were treated for another condition. GPs have an important role in the identification and referral of people with oral cancer, and the clearly recognised symptoms identified in this study can be used to aid assessment and decision-making. Interventions to promote the prompt identification of oral cancer in general practice such as the opportunistic screening of high-risk patients may help to improve the poor survival rates.